Le fondement "initiatique" du discours (post)colonial chez Ahmadou Kourouma - Almeida, José Domingues de (2014)
The author proposes an anthropological reading of the (post)colonial fact as it is distilled in the Kourouma's novels Les soleils des indépendances (1968 and 1970), En attendant le vote des bêtes sauvages (1998) and Allah n'est pas obligé (2000); which releases the relay of a complex semantic and metaphorical network of the changing status of the colonies / African countries at the time of decolonization, that is to say what Ahmadou Kourouma means by "suns" of independence. The anthropological question, especially about its initiatory ritual component, will prove not accessory or decorative, even exotic, in the work of the Ivorian writer, but a real thematic element in a more complex discursive coherence.